2016
DOI: 10.1590/1678-4685-gmb-2015-0232
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of drought-related resistance traits in Aegilops tauschii

Abstract: The D-genome progenitor of wheat (Triticum aestivum), Aegilops tauschii, possesses numerous genes for resistance to abiotic stresses, including drought. Therefore, information on the genetic architecture of A. tauschii can aid the development of drought-resistant wheat varieties. Here, we evaluated 13 traits in 373 A. tauschii accessions grown under normal and polyethylene glycol-simulated drought stress conditions and performed a genome-wide association study using 7,185 single nucleotide polymorphism (SNP) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
0
34
0
1
Order By: Relevance
“…For example, 0.23 and 0.18 were the measured values for DRS under drought and normal conditions, respectively, thus, DI = 1.28. D-values were calculated according to previously published methods (Xie, 1993;Zhou et al, 2003;Qin et al, 2016):…”
Section: Phenotypic Data Analysismentioning
confidence: 99%
“…For example, 0.23 and 0.18 were the measured values for DRS under drought and normal conditions, respectively, thus, DI = 1.28. D-values were calculated according to previously published methods (Xie, 1993;Zhou et al, 2003;Qin et al, 2016):…”
Section: Phenotypic Data Analysismentioning
confidence: 99%
“…Marker‐assisted selection (MAS) is considered to be an excellent approach for crop precision breeding, as it improves breeding efficiency and predictability, and thus accelerates breeding progress (Collard and Mackill, ).With the rapid development of next‐generation sequencing (NGS) and high‐density marker genotyping techniques, genome‐wide association study (GWAS) has become an increasingly popular and efficient method for identifying genes responsible for the quantitative variation of complex traits (Zhu et al ., ), which should be helpful in developing valuable genetic markers and performing molecular crop breeding. GWAS has been widely used for studying complex traits in various plant species such as Arabidopsis (Atwell et al ., ; Bac Molenaar et al ., ), rice (Huang et al ., ; Zhou et al ., ), maize (Li et al ., ; Yang et al ., ), Aegilops tauschii (Liu et al ., ,b; Qin et al ., ), and wheat (Liu et al ., ; Arruda et al ., ; Maccaferri et al ., ; Sukumaran et al ., ; Gao et al ., ). Progress in NGS has reduced the cost of DNA sequencing, thereby facilitating the genotyping‐by‐sequencing (GBS) of highly diverse species with large genome sizes (Elshire et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Among primary gene pool species, Ae. tauschii collections have been widely targeted for GWAS of morphological traits (Liu et al, 2015b), phosphorus deficiency (Liu et al, 2015a) and drought tolerance (Qin et al, 2016), and several genomic regions were identified. Spelt wheat (T. spelta), now gaining favour in several parts of the world (Longin and Wurschum, 2016), was also used in GWAS for agronomic and disease resistance traits using a 15K SNP array (Würschum et al, 2017).…”
Section: Genome-wide Association Studies and Genomic Predictions In Wgrmentioning
confidence: 99%